Post a New Question

algebra

posted by .

Is this correct?

subtract (4a^3+2b^3)-(6a^3+5a^2b-2ab^2+2b^3)

answer: -2a^3-5a^2b+2ab^2

  • algebra -

    correct

  • algebra -

    (2b^3-5b^2+3ab)(-3b^2)

  • algebra -

    [(-1/3a^2b^3c)^2*(-9/2ab^2c^2)+(+3/5a^4b^5c^3)^2:(-3/5a^3b^2c^2)]^2:(+11/10a^2b^8c^4)

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. Algebra

    Factor 2ab(c-d)+10d(c-d) I would like to know how to do this. Thanks. (c-d) is a common factor, so you pull it out: (c-d)(2ab + 10d) Oh, then you can pull a 2 out: (c-d)(2)(ab + 5d) Thanks! you're welcome!! What do the letters stand …
  2. factoring completly

    can anyone help me with these: 3x2 + 17x + 10 5y8 - 125 a2 - 2ab - 15b2 4c2 - 12c + 9 5 y^8 - 125 = 5(y^8 - 25) y^8 - 25 can be written (y^4 - 5)(y^4 + 5) For the others, you need to try a few factors until you find a pair that works. …
  3. algebra

    if a+b=1 and a squared + b squared=2 what does a to the 3rd + b to the 3rd equal?
  4. Math

    I don't understand how this is if (a ± b)² = a² ± 2ab + b² i would think that is would be A squared plus or minues B squared where does the 2ab come from?
  5. maths

    subtract 3a(a+b+c)-2ab(a-b+c)from 4c(-a+b+c)
  6. math 213

    Kahlil said that using the equation he can find a similar equation for Examine his argument. If it is correct, supply any missing steps or justifications; if it is incorrect, point out why. = a2 - 2ab + b2 = a2 + 2a1-b2 + 1-b22 1a …
  7. math

    Kahlil said that using the equation (a + b)2 = a2 + 2ab + b2, he can find a similar equation for (a - b)2. Examine his argument. (a - b)2 = [a + (-b)]2 = a2 + 2a(-b) + (-b)2 = a2 – 2ab + b2
  8. math

    Kahlil said that using the equation € (a + b)2 = a2 + 2ab + b2, , he can find a similar equation for € (a − b)2 . Examine his argument. If it is correct, supply any missing steps or justification; If it is incorrect point …
  9. Polynomials

    State whether the following equations are sometimes, always or never true. a) a^2-2ab-b^2= (a-b)^2, bis not equal to 0 b) a^2+ b^2= (a+b)(a+b) c) a^2-b^2= a^2-2ab+b^2 d) (a=b)^2 = a^2+2ab+b^2 I don't understand what these questions …
  10. Maths

    A polynomial g(x) is given by: g(x) = (x-1)(x+2)(x-a)(x-b) 1) Given that g(0)=4 show that ab=-2 2) given also that g(3)=40 show that a+b=1 3) given that a and b are integers, give possible values for a and b. My answers 1) g(0) = (-1)(2)(-a)(-b) …

More Similar Questions

Post a New Question